The t(X;18)(p11.2;q11.2) translocation found in human synovial sarcomas involves two distinct loci on the X chromosome. - Shipley, J; Clark, J; Crew, A; Birdsall, S; Rocques, P; Gill, S; Chelly, J; Monaco, A; Abe, S; Gusterson, B (1994)
A high proportion of synovial sarcomas contain the reciprocal translocation t(X;18)(p11.2;q11.2). We have previously localized the breakpoint on the X chromosome between the X chromosome marker DXS255 and an ornithine aminotransferase (OAT) pseudogene region designated OATL2. Subsequently by fluorescence in situ hybridization (FISH) we provided evidence that YACs corresponding to the OATL2 locus spanned the break-point. In order to confirm the position of this breakpoint cosmids corresponding to the OATL2 region were isolated. Most of these cosmids mapped to four cosmid contigs designated C1-C4. Analysis of two contigs, C1- and C4, using FISH established that in four of six synovial sarcomas examined the breakpoint occurs between these two contigs: C1 lies distal to the break-point while C4 is proximal. In contrast we provide evidence that the breakpoint in the remaining two tumours mapped to a second pseudogene region called OATL1 that is telomeric to the OATL2 locus. This heterogeneity of the breakpoint position on the X chromosome explains why in previous mapping studies there have been discrepancies between the results obtained by different laboratories.